Diastereo- and enantioselective construction of an indole-based 2, 3-dihydrobenzofuran scaffold via catalytic asymmetric [3+2] cyclizations of quinone monoimides with 3-vinylindoles. Issue 14 (19th January 2016) - Sun, Xiao-Xue; Zhang, Hong-Hao; Li, Guo-Hao; Meng, Li; Shi, Feng
Abstract : The first catalytic asymmetric [3+2] cyclization of quinone monoimides with 3-vinylindoles has been established, which constructed a biologically important 2, 3-dihydrobenzofuran framework in high stereoselectivities (up to >95 : 5 dr, 96 : 4 er). Abstract : The first catalytic asymmetric [3+2] cyclization of quinone monoimides with olefins has been established, which employed 3-vinylindoles as a class of competent olefins and spiro-chiral phosphoric acid as a powerful chiral catalyst, leading to chemo-, diastereo- and enantioselective construction of a biologically important 2, 3-dihydrobenzofuran framework with optical purity (up to 99% yield, >95 : 5 dr, 96 : 4 er).